1979
DOI: 10.1111/j.1476-5381.1979.tb07827.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Adrenaline Is Released From Adrenergic Neurones in the Rectum of the Fowl

Abstract: The rectum isolated from the fowl was perfused with Tyrode solution via the caudal mesenteric artery. Noradrenaline and adrenaline were biologically or fluorimetrically assayed in perfusates collected before and during stimulation of Remak's nerve or of the periarterial nerves. Perfusates collected during nerve stimulation relaxed the chick rectum and rat stomach strips which served as assay tissues. This effect was attributed to the action of noradrenaline or adrenaline released from adrenergic nerve endings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the rat heart, the uptake process has only about a two fold greater affinity for noradrenaline than adrenaline (Iversen, 1967). In the chicken rectum there is a 50 fold greater sensitivity to adrenaline than noradrenaline, yet blockade of uptake by phenoxybenzamine following stimulation of Remak's nerve increases the mean output of noradrenaline by only seven fold and that of adrenaline by three fold (Komori et al, 1979a). It appears unlikely therefore that the high sensitivity to adrenaline arises from an increased uptake and subsequent metabolism of noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rat heart, the uptake process has only about a two fold greater affinity for noradrenaline than adrenaline (Iversen, 1967). In the chicken rectum there is a 50 fold greater sensitivity to adrenaline than noradrenaline, yet blockade of uptake by phenoxybenzamine following stimulation of Remak's nerve increases the mean output of noradrenaline by only seven fold and that of adrenaline by three fold (Komori et al, 1979a). It appears unlikely therefore that the high sensitivity to adrenaline arises from an increased uptake and subsequent metabolism of noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of adrenaline are present in the chicken rectum (Konaka, Ohashi, Okada & Takewaki, 1979) associated with Remak's nerve (Komori, Ohashi, Okada & Takewaki, 1979a). However, information about the pharmacological characteristics of the adrenoceptors in the effector cells which would promote an understanding of the function of the adrenergic nerves in the chicken rectum, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…has been shown to be small or absent in intestinal smooth muscles (Bulbring et al, 1980). In chicken rectum, P-receptors are of the P2-type (Komori et al, 1980) and it has been demonstrated that preferential release of adrenaline rather than noradrenaline is elicited by stimulation of Remak's nerve trunk (Komori et al, 1979). Thus, this tissue is different from mammalian intestines in which pI-receptors are present (Lands et al, 1967) and noradrenaline functions as the neurotransmitter.…”
Section: P-receptor-mediated Membrane Hyperpolarizationmentioning
confidence: 99%
“…The study of neurochemicals as interkingdom signaling molecules has been termed Microbial Endocrinology ( Neuman et al, 2015 ). Like in mammals, the avian intestinal tract is a major source of many monoamine neurochemicals ( Lyte et al, 2022 ) as it is highly innervated by the enteric nervous system and contains non-neuronal endocrine cell populations ( Komori et al, 1979 ; Rawdon, 1984 ). Another similarity between the mammalian and avian intestinal microbiota are several resident bacterial taxa that synthesize and respond to structurally identical neurochemicals of the host neuroendocrine system ( Villageliu and Lyte, 2017 ).…”
Section: Introductionmentioning
confidence: 99%